2013
DOI: 10.1016/j.toxicon.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

ADP is a vasodilator component from Lasiodora sp. mygalomorph spider venom

Abstract: Members of the spider genus Lasiodora are widely distributed in Brazil, where they are commonly known as caranguejeiras. Lasiodora spider venom is slightly harmful to humans. The bite of this spider causes local pain, edema and erythema. However, Lasiodora sp. spider venom may be a source of important pharmacological tools. Our research group has described previously that Lasiodora sp. venom produces bradycardia in the isolated rat heart. In the present work, we sought to evaluate the vascular effect of Lasiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
0
12
0
4
Order By: Relevance
“…Aird [ 43 ] found that only a small number of snake venoms contained AMP compared with adenosine, but stated that the presence of purine monophosphates within venoms is unsurprising due to the hypotensive effects they share with free purines. We are unaware of previous reports of AMP, adenosine diphosphate (ADP), or adenosine triphosphate (ATP) from scorpion venoms; however, they are present within different tarantula venoms, including those belonging to H. lividum , Lasiodora sp., Aphonopelma sp., and Aphonopelma hentzi ( Dugesiella hentzi and Eurypelma californicum ) [ 30 , 33 , 52 , 66 , 67 ]. Unlike adenosine, which binds to P1 receptors, ADP and ATP bind to P2 receptors [ 68 ], with evidence suggesting that they also have auxiliary roles alongside toxins within venom [ 30 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aird [ 43 ] found that only a small number of snake venoms contained AMP compared with adenosine, but stated that the presence of purine monophosphates within venoms is unsurprising due to the hypotensive effects they share with free purines. We are unaware of previous reports of AMP, adenosine diphosphate (ADP), or adenosine triphosphate (ATP) from scorpion venoms; however, they are present within different tarantula venoms, including those belonging to H. lividum , Lasiodora sp., Aphonopelma sp., and Aphonopelma hentzi ( Dugesiella hentzi and Eurypelma californicum ) [ 30 , 33 , 52 , 66 , 67 ]. Unlike adenosine, which binds to P1 receptors, ADP and ATP bind to P2 receptors [ 68 ], with evidence suggesting that they also have auxiliary roles alongside toxins within venom [ 30 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of previous reports of AMP, adenosine diphosphate (ADP), or adenosine triphosphate (ATP) from scorpion venoms; however, they are present within different tarantula venoms, including those belonging to H. lividum , Lasiodora sp., Aphonopelma sp., and Aphonopelma hentzi ( Dugesiella hentzi and Eurypelma californicum ) [ 30 , 33 , 52 , 66 , 67 ]. Unlike adenosine, which binds to P1 receptors, ADP and ATP bind to P2 receptors [ 68 ], with evidence suggesting that they also have auxiliary roles alongside toxins within venom [ 30 , 66 ]. As with adenosine, ADP and AMP possess hypotensive properties and may fulfil a similar auxiliary function within the venom [ 8 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelium-derived nitric oxide has also been implicated in the vasodilation caused by Lasiodora sp. venom (Horta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adenosine 59-diphosphate is the principal mediator of edema caused by venom of the theraphosid Lasiodora sp. (Horta et al, 2013), whereas adenosine 59-diphosphate and ATP may actually inhibit edema caused by P. nigriventer venom (Costa et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these results suggest the participation of ERα in the endothelium-and NO-dependent relaxant effect of DGT in the rat aorta. Finally, the participation of bradykinin and P2Y receptors was tested, but neither HOE-140 (1 µM) nor suramin (100 µM), respective antagonists of bradykinin and P2Y receptors [44], induced any significant effect on the concentration-response curve to DGT (Fig. 1 S, Supporting Information).…”
mentioning
confidence: 99%